Consumo e digestibilidade aparente dos nutrientes em ovinos alimentados com dietas contendo diferentes quantidades de farelo de linhaça - Fernandes, Danieli Perez; Vieira, Paulo de Figueiredo; Rabelo, Carlos Henrique Silveira [UNESP]; Rabelo, Flávio Henrique Silveira; Salvador, Flávio Moreno; Rezende, Adauton Vilela De; Reis, Ricardo Andrade [UNESP] (My University, 2013)
The aim of this research was to evaluate the intake and apparent digestibility of nutrients in sheep fed with diets containing different amounts of linseed meal. The treatments evaluated were: corn silage exclusive (control); corn silage + concentrate; corn silage + concentrate + 5% of linseed meal; corn silage + concentrate + 10% of linseed meal. The dry matter (DM) intake has increased in diets containing concentrated if compared to diet exclusively with corn silage (P<0.05), however, there was no effect of the inclusion of linseed meal in diets (0; 5 and 10%). As it was expected, the diets containing 5 and 10% of linseed meal resulted in an increase of ether extract (EE) intake. A higher apparent digestibility of DM, organic matter (OM) and neutral detergent fiber (NDF) in the animals fed with diets containing the concentrate was observed, independently of linseed meal proportion. According to the experimental conditions under which the experiment was developed, itis recommended to provide the diets containing until 5% of linseed meal, because there is no negative effect on dry matter and nutrients intake, as well as on apparent digestibility.
Intake and apparent digestibility of nutrients in sheep fed with diets containing different amounts of linseed meal
Keywords: Animal nutrition; Energy; Fibrous fraction; Linum usitatissimum; Lipid